TAWA IN MINANGKABAU TRADITIONAL THERAPY IN THE PERSPECTIVE OF ANTHROPOLOGIC LINGUISTICS STUDIES - Usman, Fajri; Sutjaja, I Gusti Made; Meko Mbete, Aron; -, Oktavianus (e-Journal of Linguistics; Vol. 3. Juli 2009 No. 2)
The research on Tawa in Minangkabau Traditional Therapy: in the Perspective ofAnthropologic Linguistics is a research that is focused on the study of linguistic forms,functions of meaning, and the values contained in it. Qualitative approach was employedin this study. Such an approach was based on the naturalistic and interpretative paradigmwith the principles that the data were natural and interpretative in nature. To investigatethe linguistic forms, the functions, the meaning and the values, the methods employedwere “listen, get involved and talk” (simak libat cakap = SLC), “listen, not get involvedand talk” (simak bebas libat cakap = SBLC) and “talk face to face” (cakap semuka =CS). That was done by recording and taking down the narrative of tawa uttered by thedukun (healer). In order to obtain such a narration, the method of talk not face to face(cakap tak semuka = CTS), which was done by seeking for information from theinformants, was employed.The results of the thematic and schematic structure analysis show that the themeof TPTM (Tawa dalam Pengobatan Traditional Minangkabau = Tawa in MinangkabauTraditional Therapy) is related to the history of invisible creatures, the history of humanbeings, the history of animals, the history of plants, and the history of diseases). Theschematic structure of TPTM consists of introduction, content and closing. The linguistic(phonological, morphological, syntactical and semantic) forms of TPTM are related tothe use of the prosodic elements (stress, intonation and length). The morphologicalaspects of repetitions in TPTM are found in the beginning, in the beginning and centre, inthe end, and in the beginning and end of the sentences. The verbs in TPTM can be stateverbs and action verbs to which affixes are added, without and with the markers(conjunction and preposition). In syntactical level, the sentence structure in TPTM is notgenerally the same as that in Minangfkabau language. Statements, imperatives, andprohibitions dominate the sentences in TPTM. In addition, the omission of subjects andobjects, and the existence of parallelism, when creating rhythmic units, functioning toraise musical sounds for inviting magical powers feature TPTM.
Keywords: Tawa, disease, traditional therapy, anthropologic linguistics